A critical appraisal of Zakir Naik’s Islamic evangelism - Mustapha, Maziah; Abdul Razak, Mohd Abbas (Department of Theology and Philosophy, National University of Malaysia (Universiti Kebangsaan Malaysia) and the International Society of Muslim Philosophers and Theologians (ISOMPT), 2019)
Though Islam is a religion against compulsion in inviting others into its fold, but it allows to a certain degree for Muslim scholars to engage in any form of peaceful, ethical and intellectual debate/discourse with people of other faith. Ever since this message was communicated through the Qur’an, there appeared in the Muslim world many intellectuals who engaged people of other faith in discussing issues related to God and spirituality. While the Muslim world still celebrates the contribution of past renowned Muslim scholars in the area of comparative religion, this small-scale research is designed to investigate the approaches, contributions and controversies that surround Naik who is a contemporary Muslim scholar of comparative religion. Even though many recognize his intellectual competency in discussing other religions, but there are people around the globe who find his public lecture provocative, cynical and disparaging towards other religions. Through this qualitative study, the researchers intend to conduct a critical appraisal on Naik’s religious propagation. Besides that, the researchers will also analyze some of the criticisms hurled at him. The critical analysis of the research will objectively discuss Naik’s method of preaching, personality, style of public lecture, etc. The Textual-Analysis method will be employed to interpret the pertinent data of this research that come in the form of Naik’s public lectures and written documents.